1996
DOI: 10.1364/ol.21.001168
|View full text |Cite
|
Sign up to set email alerts
|

Self-pumped phase conjugation with femtosecond pulses by use of BaTiO_3

Abstract: Self-pumped phase conjugation is generally believed to be attributed to degenerate four-wave mixing. Accordingly, the phenomenon requires the existence of three waves at certain interaction regions for the excitation of the fourth one. Although this condition is not satisfied by a train of femtosecond pulses with a repetition rate of 110 MHz, we have observed self-pumped conjugate pulses retroref lected by a BaTiO(3) crystal. The conjugate character of the pulses is demonstrated with the distorter method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…National Research Laboratory of Metrology, Tsukuba, Ibaraki 305 Japan ͑Received 10 August 1998; accepted for publication 9 February 1999͒ We report the generation and characterization of the self-pumped phase conjugation of 450 nm femtosecond pulses in BaTiO 3 . The pump beam is incident on the crystal from the Ϫc face of the crystal.…”
Section: K Minoshima K Seta and H Matsumotomentioning
confidence: 99%
See 3 more Smart Citations
“…National Research Laboratory of Metrology, Tsukuba, Ibaraki 305 Japan ͑Received 10 August 1998; accepted for publication 9 February 1999͒ We report the generation and characterization of the self-pumped phase conjugation of 450 nm femtosecond pulses in BaTiO 3 . The pump beam is incident on the crystal from the Ϫc face of the crystal.…”
Section: K Minoshima K Seta and H Matsumotomentioning
confidence: 99%
“…[1][2][3][4][5][6] demonstrated highefficiency phase conjugation of broadband pulses in photorefractive crystals with a dispersive ''2-f '' system. Lobel, Petersen and Johansen 6 showed that the frequency scanning of the self-pumped phase conjugation ͑SPPC͒ could be avoided if the material dispersion of the photorefractive crystal was compensated by external dispersion devices, such as prisms and/or gratings.…”
Section: K Minoshima K Seta and H Matsumotomentioning
confidence: 99%
See 2 more Smart Citations
“…Femtosecond self-pumped phase conjugation (SPPC) at various wavelengths has been observed in BaTiO 3 . [18][19][20][21][22][23] But its temporal characteristics have not been investigated yet. Although Yariv et al 24 proposed that the process of nonlinear optical phase conjugation could be utilized to compensate for channel dispersion, they discussed only the phase conjugation achieved by four-wave mixing in nondispersive media.…”
Section: Introductionmentioning
confidence: 99%